Perlindungan Hak Anak Yang Menjadi Pelaku Tindak Pidana Pencurian Dalam Putusan Pengadilan Negeri Magetan Nomor : 4/Pid.Sus-Anak/2021/PN.Mgt - Krista Yitawati; Bambang Sukarjono; Adi Nur Rahim Tri Wi Joyo; Meirza Aulia Chairani (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2022)
Abstract- This study aims to determine the protection of the rights of children who are perpetrators of the crime of theft in the Magetan District Court Decision Number: 4/Pid.Sus-Anak/2021/PN.Mgt. The type of legal research used is normative, research that focuses on positive law in the form of legislation and this research requires secondary legal material as the main legal material. The results showed that the elements of the article that had been fulfilled as stated in the single indictment, namely Article 363 paragraph (1) to the 3rd, 4th, and 5th of the Criminal Code. The judge stated that the children had been legally and convincingly proven guilty of committing the crime of theft. with weighting. The decision taken by the judge in the decision Number: 4/Pid.Sus-Anak/2021/PN.Mgt is not solely made based on legal considerations, but also the surrounding conditions, social status of children, and family circumstances that prioritize the Restorative Justice approach.